PRIORITAS PEMILIHAN LOKASI PENGEMBANGAN PELABUHAN PERIKANAN DI KABUPATEN REMBANG - Iin Solihin; Muhammad Syamsu Rokhman (Buletin PSP, 2009)
The background of this research is needed location selection priority to the  fishing port development in one region.  Defining this priority is important because 1) there is restricted allocation fund to the fishing port development and 2) the fishing port has been existence that can be influenced to other fishing port development.  This objective research is defining the  fishing port development priority at Rembang Regency and using Analytical Hierarchy Process Method  to achievethis objective.  Research result indicates that Tasik Agung coastal fishing port is main priority  to develop, and the further priorities are Sarang Medur fish landing place, Karang Anyar fish landing place, Tanjungsari fish landing place and Pandangan fish landing place.  The program to develop Tasik Agung coastal fishing port are investment development, and fisheries business.  Key words:  development, fishing port, priority